PENGARUH MEDIA PAPAN HURUF CERIA TERHADAP KEMAMPUAN MEMBACA ANAK DI TAMAN KANAK-KANAK BHAKTI BUNDA PADANG - Tira Desmalianti; Yulsofriend; Dadan Suryana; Saridewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early reading skills in young children require appropriate stimulation through engaging learning media that match the child’s developmental level. Reading ability is a crucial aspect of language development that should be introduced early so children can properly recognize letters, syllables, and simple words. Therefore, reading skills are important to introduce in early childhood. At Taman Kanak-kanak Bhakti Bunda Padang, some children’s reading abilities have not yet developed optimally, and the learning media used remain limited in variety and fail to attract the children’s attention. This problem indicates that the design of reading instruction should be made more engaging and effective for children. The study employed a quantitative experimental design. The population consisted of 42 children. The research used a quasi-experimental design with cluster sampling, where samples were selected based on specific considerations required for the study. Hypothesis testing employed the Paired Sample T-test with a significance level of 0.05. The results show that the use of the “Papan Huruf Ceria” media has a positive effect on the children’s reading ability at Taman Kanak-kanak Bhakti Bunda Padang. This is evidenced by an increase in learning outcomes from pre-test to post-test scores; additionally, the significance value (2-tailed) was 0.001.